2003
DOI: 10.1128/jvi.77.10.5846-5854.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evolution of Human Immunodeficiency Virus Type 1 toward Increased Pathogenicity through CXCR4-Mediated Killing of Uninfected CD4 T Cells

Abstract: The destruction of the immune system by progressive loss of CD4 T cells is the hallmark of AIDS. CCR5-dependent (R5) human immunodeficiency virus type 1 (HIV-1) isolates predominate in the early, asymptomatic stages of HIV-1 infection, while CXCR4-dependent (X4) isolates typically emerge at later stages, frequently coinciding with a rapid decline in CD4 T cells. Lymphocyte killing in vivo primarily occurs through apoptosis, but the importance of apoptosis of HIV-1-infected cells relative to apoptosis of uninfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(124 citation statements)
references
References 51 publications
3
117
2
2
Order By: Relevance
“…Hence, the hypothesis that gp41-mediated hemifusion results in bystander cell death may not be just an in vitro effect but also correlates with in vivo clinical findings and has implications for Enfuvirtide therapy. The nat- ural progression of HIV disease results in the selection of more pathogenic (42) and probably more fusogenic Env proteins as a selection for viral fitness. However, the use of Enfuvirtide therapy to select less fusogenic and consequently less pathogenic viruses may be beneficial to patients, even after failure of Enfuvirtide therapy to control virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the hypothesis that gp41-mediated hemifusion results in bystander cell death may not be just an in vitro effect but also correlates with in vivo clinical findings and has implications for Enfuvirtide therapy. The nat- ural progression of HIV disease results in the selection of more pathogenic (42) and probably more fusogenic Env proteins as a selection for viral fitness. However, the use of Enfuvirtide therapy to select less fusogenic and consequently less pathogenic viruses may be beneficial to patients, even after failure of Enfuvirtide therapy to control virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[8][9][10] The third proposed mechanism is excessive, ongoing immune activation caused by a high, persistent viral antigen load and leading to the activation-induced death of various uninfected immune cells, including CD4 þ T cells. 1,2,4,8,9 Evidence for the involvement of indirect mechanisms of CD4 þ T-cell killing has been provided by the identification in vivo [11][12][13][14][15][16] and ex vivo [17][18][19] of increased number of dying, uninfected immune cells, including CD4 þ T cells, both in HIV1-infected persons and in non-human primate models of pathogenic simian immunodeficiency virus (SIV) infection, that are closely related to HIV. An important question is whether HIV1 may only cause death in activated, cycling CD4 þ T cells, or also in unstimulated noncycling CD4 þ T cells, which represent at any given time point the vast majority of the CD4 þ T cells in HIV1-infected persons.…”
Section: Introductionmentioning
confidence: 99%
“…3 Because most of the viral particles produced during HIV1 infection are replication-defective, 6 but can still bind to-, and enter into-CD4 þ T cells, viral proteins present at the surface or inside the viral particles have been proposed as candidates for the killing of noncycling CD4 þ T cells in the absence of productive infection of these cells. In vitro findings have suggested that among such viral proteins, the HIV1 surface envelope (Env) constitutes a major potential candidate for the HIV1-mediated killing of CD4 þ T cells in the absence of productive infection, 16,[20][21][22][23][24][25][26] through death signaling caused by engagement of either its cell-surface receptor, CD4 [27][28][29] or, for the Env of X4-tropic HIV1 strains, of its CXCR4 coreceptor. 25,26,30,31 Incubation of noncycling, primary CD4 þ T cells with X4-tropic HIV1 viral particles has been previously reported to cause CD4 þ T-cell death, after a delay of 3-4 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…180 When HIV translates into the more advanced AIDS, CXCR4 becomes the more relevant receptor. 181 Although potent inhibitors of CXCR4 exist, their clinical utility is limited by severe side effects. Indeed, since CXCR4 or CXCL12 knockout mice are not viable, significant doubt remains over whether this pathway can be safely manipulated in the long term.…”
Section: Chemokines As Therapeutic Targetsmentioning
confidence: 99%